THEORETICAL ASPECTS OF LIGHTWEIGHT HELIPAD PAVEMENT CALCULATION - Bliznyuk, Taras (Proceedings of National Aviation University (archive), 2014)
The article focuses on the calculation of mobile heliport and airport pavement. Benefits anddisadvantages of using steel plates as a pavement material and history of its development are presented. Basiccalculation relations, which could be used in the development of standard calculation procedure of mobile pavements,are also given.